Effect of black tea consumption on onset of action of benzodiazepines in children: A case–control study - Mishra, Nihar Ranjan; Panda, Prakash Chandra (Indian Journal of Child Health, 2022)
Introduction: Benzodiazepines (lorazepam and diazepam) are the drugs that have calming effects, but caffeine of black tea is a stimulant. Hence, taking black tea along with benzodiazepines might block the calming effects of the latter. In our locality, giving black tea to the children is a regular sociocultural practice by their parents. Objective: To know the effect of black tea consumption on onset of action of benzodiazepines in children. Methods: An observational analytic matched case–control study was done in our department from January 2015 to June 2015 subjected to interview schedule by simple consecutive sampling, and data were analyzed using SPSS version 24 software after proper consent and ethical committee approval. Inclusion criteria of cases were any child taking black tea routinely between 1 and 15 years of age attending our outpatient department or inpatient department requiring intravenous (IV) benzodiazepines medications, and exclusion criteria were critically ill children, having chronic liver or kidney diseases, and children taking anticonvulsants regularly. Children of identical age groups, not taking black tea at all, requiring IV benzodiazepines were taken as controls. Results: An independent t-test showed a significant difference in the onset of action of lorazepam in black tea drinkers (M=5.44 h, standard deviation [SD]=2.43h) and in non-drinkers (M=1.65 h, SD=0.74h); t (99.06)=13.94h, p=0.016 and for diazepam in drinkers (M=1.65 h, SD=0.74h) and in non-drinkers (M=0.93 h, SD=0.37h); t (98.23)=16.58h, p=0.005. Conclusion: Black tea delays the onset of actions of benzodiazepines. Hence, it is advisable not to give black tea to the children, and further studies on this aspect are warranted.